Andreev-reflection spectroscopy with superconducting indium - a case study - Gloos, Kurt; Tuuli, Elina (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We have investigated Andreev reflection at interfaces between superconducting indium (Tc = 3.4 K) and several normal conducting nonmagnetic metals (palladium, platinum, and silver) down to T = 0.1 K as well as zinc (Tc = 0.87 K) in its normal state at T = 2.5 K. We analyzed the point-contact spectra with the modified onedimensional BTK theory valid for ballistic transport. It includes Dynes’ quasiparticle lifetime as fitting parameter Γ in addition to superconducting energy gap 2Δ and strength Z of the interface barrier. For contact areas from less than 1 nm2 to 10000 nm2 the BTK Z-parameter was close to 0.5, corresponding to transmission coefficients of about 80%, independent of the normal metal. The very small variation of Z indicates that the interfaces have a negligible dielectric tunneling barrier. Also Fermi surface mismatch does not account for the observed Z. The extracted value Z ≈ 0.5 can be explained by assuming that practically all of our point contacts are in the diffusive regime.